Mammoth skeleton in Yakutsk, Russia ... - Campbell, Sady (University of Alberta Library, 2014)
Display of a mammoth skeleton (frontal view) at the Mammoth Museum, Severo-Vostochnyy Federal'nyy Universitet Im. M.k. Ammosova, Yakutsk, Sakha Republic, Russia, ...